The Influence of Influencer Credibility and Message Type on Consumer Purchase Intention: The Mediating Role of Attitudes Toward Influencers - Pradana, David Arya Veri; Ridanasti, Erlita (Dinasti Publisher, 2026)
This study examines the influence of influencer credibility and message types on consumer purchase intention through attitude toward influencer. The purpose of this research is to understand how the credibility of influencers and the types of message delivered in social media promotions shape consumer attitudes and influence their intention to purchase promoted products. This study adopts a quantitative approach using Partial Least Square (PLS) analysis with SmartPLS version 4.0. Data were collected through a questionnaire from 200 respondents. The findings indicate that influencer credibility, which consists of attractiveness, trustworthiness, and expertise, has a positive and significant effect on purchase intention. In contrast, message types, including informative value and entertainment value, do not have a direct effect on purchase intention. However, both influencer credibility and message types significantly influence attitude toward influencer. Furthermore, attitude toward influencer has a positive and significant effect on purchase intention. These findings highlight the importance of influencer credibility in shaping consumer attitudes and encouraging purchase intention. They study provides insights for marketers to design more effective influencer marketing strategies by focusing on credible influencers and engaging message delivery.